The challenge of child undernutrition in Uttar Pradesh: Findings from a situation assessment - Menon, Purnima; Kohli, Neha; Pradhan, Mamata; Pradhan, Niru; Cyriac, Shruthi; Priyadarshi, Meera (International Food Policy Research Institute, 2014)
This paper analyzes the current nutrition situation in Uttar Pradesh and examines nutrition-related services, programs, and policies with the goal of informing strategic directions for nutrition-related policy in Uttar Pradesh. This paper uses an assessment framework that explicitly considers the biological, programmatic, and sociopolitical aspects of nutrition in Uttar Pradesh.